Trophic structure and soil depth stratification as ecological drivers of taxonomic and species diversity in the nematode community in Central Asian peach orchards - Dilnoza M. Nurmatova; Sardorbek B. Narzullayev; Ochil Mavlyanov; Naimitdin Khakimov; Abdurashid R. Jabborov; Komil S. Boltayev; Uktam N. Mirzaev; Abbos A. Ashrapov; Shahlo S. Tursnunova; Shakhboz Khujamov (Acta Biologica Sibirica, 2025)
The formation of nematode communities and their drivers remain poorly understood in arid agroecosystems, particularly in Central Asia’s intensive orchards. We investigated nematode fauna in peach orchards of Uzbekistan’s Zarafshan Valley (2023–2024), where low-organic soils (0.9–1.3% OM) and monoculture practices create unique ecological constraints. From 180 samples (149 nematode-positive), we identified 61 species across 38 genera, including Butlerius butleri Goodey, 1929 (Rhabditida) as a new country record. The study revealed clear patterns in how nematodes distribute themselves across different habitats within peach orchards. Root systems showed a strong preference for endoparasitic nematodes like Meloidogyne and Pratylenchus, which were found to be 9.2 times more likely to occur in roots compared to soil. Meanwhile, the soil layers hosted the majority (85.7%) of bacterivorous nematodes, though their populations decreased significantly with depth – diversity indices dropped from 3.88 in the top 0–15 cm layer to 3.81 in the 15–30 cm layer. Interestingly, while the types of nematode species remained quite similar between soil layers (with a 92% similarity index), their actual numbers varied considerably, suggesting that environmental conditions primarily affect population sizes rather than species presence. Several key environmental factors emerged as important drivers of these distribution patterns. Organic matter content stood out as the strongest predictor, accounting for 51% of the variation in nematode diversity, followed closely by soil bulk density at 43%. Soil chemistry also played a significant role, with pH and nutrient levels (N, P, K) showing moderate to strong correlations (0.58–0.64) with nematode abundance. Some nematode groups displayed remarkable adaptability – omnivorous species like Eudorylaimus showed no particular depth preference, maintaining consistent populations throughout the soil profile. These findings provide important ecological insights about soil communities in agricultural systems. The feeding habits of nematodes explained about 18% of how communities were structured, revealing how agricultural practices create different nematode communities compared to natural ecosystems. One of the most striking observations was that changes in soil depth affected nematode numbers 2.3 times more strongly than they affected which species were present. This suggests that farming practices likely influence nematode communities more by changing population sizes than by eliminating particular species, with soil quality parameters like organic matter and compaction being particularly important factors shaping these communities.